Sun, wind, and light: architectural design strategies - Brown, G. Z.; DeKay, Mark. (2013)
"This fully updated Third Edition covers principles of designing buildings that use the sun for heating, wind for cooling, and daylight for natural lighting. Using hundreds of illustrations and companion CD-ROM, this book offers practical strategies that give the designer the tools they need to make energy efficient buildings"--
Machine generated contents note: WHAT'S ON THE DVDI THE SUSTAINABLE DESIGN NAVIGATOR Using the Sustainable Design Navigator an electronic tool for design advice queries 28 Analysis Techniques, 8.5 x 11 printable 90 Design Strategies, 8.5 x 11 printable Indexes, searchable Bibliography, searchableII SUSTAINABLE DESIGN RESOURCES Sun Charts and Sundials Climate Data and Analyses Energy Scheming 3.5 software, demo version Additional ResourcesWHAT'S IN THE PRINTED BOOKIII NAVIGATION Abbreviated Contents for the Printed Book Abbreviated Contents for the DVD Detailed Contents for the Printed Book Detailed Contents for the DVD Additional Navigation MethodsIV USING SUN, WIND & LIGHT The Energetic Design Process Net-Zero Energy and Carbon-Neutral Design Selecting Bundles and Making Your Own Using the Sustainable Design NavigatorV THE FUNDAMENTAL BUNDLESVI QUICK DESIGN GUIDELINESVI TOP 25 DESIGN STRATEGIES Appendix Bibliography Indexes.
Includes index.
Keywords: Architecture and energy conservation; Architecture and solar radiation; Interior lighting; ARCHITECTURE / Methods & Materials